An approach to telmophagous Nematocera (Ceratopogonidae, Psychodidae, and Simuliidae) of Spain, with emphasis on its medical and veterinary importance - Alarcón-Elbal, Pedro María; González, Mikel Alexander (InterAmerican Journal of Medicine and Health, 2023)
Nematocera are a suborder of Diptera which historically influenced human history more than any other arthropod group. Four families show a hematophagous behaviour, one being solenophagous (Culicidae), feeding directly on blood vessels, and three being telmophagous (Ceratopogonidae, Psychodidae, and Simuliidae), feeding on blood which pools at the site where their mouthparts have formed a laceration. Although mosquitoes rank first in importance, the telmophagous are also of great interest. Objectives: to update the status of these nematocerans through a transdisciplinary approach, reviewing the main characteristics of each family, the situation of the main vector-borne diseases transmitted by them in the country, especially during the 21st century, and the most relevant species or species groups from a medical and veterinary perspective. Methods: a literature search of databases was conducted and supplemented by browsing specialized journals and citation searching. Results were reviewed and filtered. Results: to date, 84 species of biting midges (Ceratopogonidae), 13 species of sand flies (Psychodidae), and 53 species of black flies (Simuliidae) have been reported in Spain. Culicoides imicola and the Obsoletus complex stand out as the most important biting midges, as they are incriminated in the transmission of bluetongue and Schmallemberg virus; Phlebotomus perniciosus and Phlebotomus ariasi are the vectors of Leishmania infantum; and Simulium erythrocephalum and the Ornatum complex cause the greater part of nuisance and bites to humans in Spain. Conclusions: there is a need to increase research capacity in Spain in order to address several health challenges arising from the presence of telmophagous Nematocera in particular, and of blood-sucking atropods in general.